Dietary Practices and Associated Factors Among Adult Diabetic Patients at Academic Tertiary-Level Hospitals in Central Ethiopia: Convergent Mixed Study - Sentayehu Admasu Saliya MSc; Taye Mezgebu Ashine MSc; Asnakech Zekiwos Heliso MSc; Getachew Ossabo Babore MSc; Bethelhem Birhanu MSc; Awoke Girma Hailu MSc; Sisay Foga Sebro MSc; Elias Ezo MSc; Selamawit Wondale Begizew MSc (SAGE Publishing, 2024)
Background Diabetes mellitus (DM) is one of the most common chronic diseases globally. Despite the presence of national strategies to prevent potential sequelae DM has been associated with increased morbidities and mortality in Ethiopia, and the prevalence appears to be on the rise. Although studies have been conducted among DM patients in the country, there is a lack of information that could allow an in-depth understanding of the situation. Objective To assess dietary practices and associated factors among adult DM patients at academic tertiary-level hospitals in central Ethiopia. Methods The institution-based concurrent mixed-methods study was conducted from January 01 to 30 2024 involving 420 adult DM patients. Participants were selected using a simple random sampling technique for quantitative study. A purposive sampling technique was used to select 16 participants for qualitative analysis. For the quantitative study, a self-administered structured questionnaire was used to collect data, and an in-depth interview for the qualitative part. Multivariate binary logistic regressions were used to assess the explanatory variables associated with dietary practice. A thematic analysis was performed for qualitative data. Result Of 420 eligible participants, 406 (96.7%) participated in the study. The overall proportion of good dietary practices among participants was 172 (44.2%). The being female, urban residence a family history of DM, and good dietary were significantly associated with the dietary practice. From qualitative analysis, two themes have emerged; Living as before and not adhering to diabetic dietary recommendations and barriers to adherence to effective eating practice. Conclusions and recommendations Less than half of adult DM patients had good dietary practices. Sex, geographic location, family history of DM, and level of knowledge of diabetic diet were associated with dietary practice. Intervention programs on awareness creation and training to improve the dietary practice by stakeholders were recommended.